PENGARUH EDUKASI KESEHATAN TERHADAP PENGETAHUAN DISMENOREA PRIMER DISERTAI PERILAKU SWAMEDIKASI PADA MAHASISWI SEKOLAH TINGGI ILMU TARBIYAH MADANI YOGYAKARTA - Wijayanti, Annisa Jihan; Kautsari, Farah Widya (Jurnal Kesehatan Madani Medika, 2025)
The prevalence of dysmenorrhea in Indonesia, particularly in Yogyakarta, remains relatively high, ranging from 60% to 70%, with an estimated rate of 64.25%. This consists of 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea, with the highest prevalence found among adolescents aged 17 to 24 years. This study aimed to determine the effect of health education on knowledge of primary dysmenorrhea and self-medication behavior, as well as to analyze the relationship between these variables. The study employed a pre-experimental design with a one-group pre-test–post-test approach. Educational intervention was delivered through direct material presentation. Data were collected using a non-probability purposive sampling technique according to inclusion and exclusion criteria. Statistical analysis was conducted using the Wilcoxon Signed-Rank Test and Spearman’s rho correlation test. The results showed that the Wilcoxon Signed-Rank Test indicated a significant improvement in participants’ knowledge following the educational intervention (p = 0.000 < 0.05). Furthermore, the Spearman’s rho correlation test revealed a significant relationship between knowledge of primary dysmenorrhea and self-medication behavior (p = 0.000 < 0.05). Based on these findings, it can be concluded that health education significantly increases knowledge regarding primary dysmenorrhea and demonstrates a positive relationship between knowledge and self-medication behavior among female students at Madani Tarbiyah College, Yogyakarta.